An Assessment of the Regulatory Powers of the National Agency for Food and Drugs Administration Council in the Protection of Consumers of its Regulated Products in Nigeria (Global Journal of Management and Business Research, 2017)
Food, Drugs and Drinks are essential requirements of human existence. The volume of business involved in the supply of these necessaries is very high and profitable. If left unregulated, manufac- turers and suppliers of these products may engage in underhand business stratagems in order to maximize their profits whilst endangering the life of the consumers. This article examines the powers and functions of the regulatory agency in Nigeria for the control of manufacturers and suppliers of food, drugs and drink products in the country. The aim is to determine the level of protection afforded to consumers of these regulated products in the country. Our research methodology is basically doctrinaire and analytical and in the end it was discovered that in spite of the deluge of laws and regulations aimed at protecting consumers in the sector in Nigeria, they are still far from beingad equately protected. This article makes some suggestions for improvement in this regard.
Keywords: suppliers of food; drugs and drink products